2015
DOI: 10.1177/1541931215591285
|View full text |Cite
|
Sign up to set email alerts
|

Provider Workflow and Patient Care

Abstract: Healthcare provider workflows for documenting and tracking patients, hitherto predominantly manual and paper-based, have recently become significantly computerized. Computerization has made the storage, processing and retrieval of information easier. However, it has increased the potential for errors, impacted direct patient care, and burdened providers with documentation. This paper describes a study to understand information use among providers in intensive care units, and inpatient and outpatient units. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…The AMWT and AMJT decreased significantly while TMV increased hence, reflecting an improvement in operations and possibly, patient satisfaction. A similar trend is also observed in a number of HIC studies (39,40,47,48). This positive trend could also be linked to the functionality, user interface and operability of the EHIMS which was designed to suit low-resource settings and primary facilities (levels 2 and 3).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The AMWT and AMJT decreased significantly while TMV increased hence, reflecting an improvement in operations and possibly, patient satisfaction. A similar trend is also observed in a number of HIC studies (39,40,47,48). This positive trend could also be linked to the functionality, user interface and operability of the EHIMS which was designed to suit low-resource settings and primary facilities (levels 2 and 3).…”
Section: Discussionsupporting
confidence: 86%
“…A previous internal evaluation study in Kenya, conducted shortly after launching revealed that, the adoption of this software improved operational performance by reducing admission length and patient waiting times, and also increased productivity of staff and patient turnover (38). As demonstrated in HICs, it has been shown that better operational performance can lead to improved financial performance by increasing insurance reimbursements, decreasing operating costs and reducing the waste of resources (39,40). However, this study used considerably fewer data.…”
Section: Introductionmentioning
confidence: 96%